Meningkatkan Kemampuan Pemahaman Matematis Siswa Melalui Model Problem Based Learning di SMA Negeri 2 Medan - Yusni Utami; Hidayat Hidayat; Haryati Ahda Nasution; Yuki Indayanti (Departement of Mathematics Education, 2024)
Mathematics is a vital discipline, yet it is often considered complicated by students. This results in their low mathematical understanding, which is very important in learning mathematics to solve problems more easily and relate the concepts understood. “This study used a class action research method (PTK) on students of class XI IPA-3 SMA Negeri 2 Medan in the 2023/2024 academic year, totaling 36 people. In this study, data were collected through observation sheets, learning outcome tests, and documentation to evaluate the mathematical understanding ability of students in class XI-IPA 3 at SMA Negeri 2 Medan. The results showed a significant improvement after the application of the Problem Based Learning (PBL) learning model, as seen from the results of the initial ability test, cycle I test, and cycle II test”.